KONFIGURASI POLITIK DAN KARAKTER HUKUM DALAM PERUMUSAN PERJANJIAN KERJA PERORANGAN DAN PERJANJIAN KERJA BERSAMA (Universitas Suryakancana, 2018)
The creation of employment and strive through the clarity of the rights and obligations of the parties (worker/workers and employers), to clarify the rights and obligations of the parties in industrial relations, both regarding the rights and obligations are the norms of work (Labour Legislation) as well as the nature of Work Terms (Terms of Employment), need a means of industrial relations in the form of Individual Work Agreements (PKP) who apply individually and joint work Agreement (PKB) who collectively apply. The problem examined concerns the political configuration of the legitimately in the manufacture of PKP and PKB. Research methods in this study using a descriptive analytical. The research results obtained that the making of PKP applies should be qualified legitimately an agreement as provided for in article paragraph (1) 1320 s. d subsection (4) the book of the law of civil law (KUHPerdata), and specifically the process of formulation of the PKB should match the concept of the Welvaartsstaat with the character of the legal product PKB responsive/populistik.Keywords: Political Configuration, Individual Work Agreements, Joint Work Agreement.